Establishment and characterization of a continuous cell line from caudal fin of Labeo calbasu (Hamilton, 1822). (10th May 2022) - Yadav, Manoj K.; Rastogi, Aakriti; Verma, Dev K.; Paria, Anutosh; Kushwaha, Basdeo; Rathore, Gaurav; Swaminathan, T. Raja; Pradhan, Pravata K.; Sood, Neeraj
Abstract: Labeo calbasu is an important food fish and candidate species for diversification of carp aquaculture. In the present study, we have established a continuous cell line, designated as L. calbasu fin (LCF), from caudal fin of L. calbasu using explant method. The cell line has been subcultured for over 73 passages and the LCF cells show optimal growth in Leibovitz's L‐15 medium supplemented with 20% fetal bovine serum at a temperature of 28°C. In karyotype analysis, the modal chromosome number of LCF cells at 35th passage was found to be 50. The amplification and sequencing of partial fragments of mitochondrial genes, namely 16S rRNA and COI from LCF cells confirmed the origin of cell line from L. calbasu . The LCF cells could be successfully transfected with GFP reporter gene, indicating suitability of these cells for expression of foreign genes. Further, following inoculation with supernatant from Tilapia lake virus (TiLV) infected cell line, no cytopathic effects were observed in the LCF cells and cell pellet was negative for TiLV in RT‐PCR, indicating that LCF cells were not susceptible to TiLV. The developed cell line has been submitted to National Repository of Fish Cell Lines being maintained at ICAR‐National Bureau of Fish Genetic Resources, Lucknow (accession no. NRFC063). The newly developed LCF cell line would be helpful in investigating diseases affecting this candidate species particularly the ones suspected to be of viral etiology, and for cytotoxicity and transgenic studies.